Social Security Wealth and Wealth Accumulation: Further Microeconomic Evidence - Novos, Ian E. (The Review of Economics and Statistics, 1989)
This study involves an empirical analysis of the effect of social security wealth on wealth accumulation. My analysis takes as its point of departure a study by Feldstein and Pellechio on this subject. Their study used the same data source as analysed in this paper. Feldstein and Pellechio found strong support for the notion that increases in social security wealth caused families to reduce their wealth accumulation. My resuts indicate the strong conclusions reached by Feldstein and Pellechio are not robust. In particular, first, when I excluded a group, of farmers from our sample increases in social security wealth did not result in families reducing their wealth accumulation. Second, Feldstein and Pellechio calculated social security wealth using income measures from a single year. When I applied their methodlogy to income measures from a different year results were markedly affected.